Increased PD‐L1 expression in breast and colon cancer stem cells. (May 2017) - Wu, Yanheng; Chen, Mingshui; Wu, Peihong; Chen, Chen; Xu, Zhi Ping; Gu, Wenyi
Summary: Here we report the expression of programmed cell death ligand 1/2 (PD‐L1/L2) in breast and colon cancer stem cells (CSCs). The stemness of these cells was confirmed by their surface markers. Using flow cytometry analysis we demonstrated that PD‐L1 expression was higher in CSCs of both cancers compared to non‐stem like cancer cells. Consistent with this, detection of cellular PD‐L1 proteins by western blot assay also showed increased PD‐L1 protein in CSCs. In contrast, only trace amounts of PD‐L2 were detected in CSCs of both cancers. Our results suggest that breast and colon cancers may be sensitive to PD1/PD‐L1 immunotherapy and thus warrant further investigations of CSC targeted PD1/PD‐L1 therapy.